2022
DOI: 10.48550/arxiv.2201.01877
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A quantitative assessment of Imaging High-Z and Medium-Z materials using Muon Scattering Tomography

Abstract: A: Muon Scattering Tomography (MST) has been shown to be a powerful technique for the non-invasive imaging of high-shielded objects. We present here the application of the MST technique to investigate two types of nuclear waste packages, a small-steel drum and a large nuclear waste cask, namely, a CASTOR V/52. We have developed a quantitative method using the contrast-to-noise ratio (CNR) to evaluate the performance of an MST detector system in differentiating between high-, medium-, and low-Z materials inside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Extensive research has shown that MT has a wide range of applications, including the imaging of volcanoes [1,2], pyramids [3,4], hidden underground structures [5,6], nuclear reactors [7,8], high-Z materials [9], high-Z and medium-Z materials [10], and bedrock sculpting beneath an alpine glacier [11]. The imaging techniques used in MT are often based on plastic scintillators [12,13], emulsion [14], and gas [15] detectors.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has shown that MT has a wide range of applications, including the imaging of volcanoes [1,2], pyramids [3,4], hidden underground structures [5,6], nuclear reactors [7,8], high-Z materials [9], high-Z and medium-Z materials [10], and bedrock sculpting beneath an alpine glacier [11]. The imaging techniques used in MT are often based on plastic scintillators [12,13], emulsion [14], and gas [15] detectors.…”
Section: Introductionmentioning
confidence: 99%